The Effect of Directed Reading Activity (DRA) Strategy on the Students’ Reading Comprehension at Madrasah Aliyah Negeri 1 Pekanbaru - Yusniar Yusniar (Instructional Development Journal, 2021)
Many students at MAN 1 Pekanbaru have problem in reading comprehension that should be mastered by them in English subject. To solve the problem, Directed Reading Activity (DRA) strategy was offered to improve the students’ reading comprehension. The main objective of this research was to find out the significant effect of using Directed Reading Activity (DRA)  strategy. Sixty two students MAN 1 Pekanbaru participated in study. In collecting data used a test while in analyzing the data used an independent sample t-test an a pair simple t-test. The result of data analysis has identified that after conducting the treatment could improve 71,37% on reading comprehension in narrative text of students MAN 1 Pekanbaru. It meant that there was significant effect of using Directed Reading Activity strategy on students’ reading comprehension.Keywords: